Birds of the West Indies - Raffaele, Herbert A. (Book collections on Project MUSE., 2003)
Fully illustrated, easy to use, and completely up-to-date, Birds of the West Indies is the only field guide that covers all of the bird species known to occur in the region--including migrants and infrequently occurring forms. Each species is represented by a full description that includes identification field marks, status and range, habitat, and voice. A map showing the bird's distribution accompanies many species accounts, and plumages of all species are depicted in ninety-three beautifully rendered color plates. Bird lovers, vacationing tourists, local residents, and ""arm.